RANCANG PURWARUPA SMART DIGITAL-WALLET BERBASIS PURWARUPA MOBILE UNTUK SPBU MANDIRI - Meredita Susanty; Rahmat Septian Wijanarko (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
As a commitment for service improvement, Pertamina provides self-service gas station to reduce queue time and various non-cash payment methods such as debit and credit cards in cooperation with various banks, or subscription cards such as Gazcard which is issued by Pertamina. Nonetheless, these two services have not been integrated. Cashless payment is only available at conventional gas stations. This research proposes a new payment method for self-service stations using digital-wallet, a mobile-based applications, which will overcome the limitations of the existing payment methods at self-service gas station in terms of the guarantee payment for each transaction even when there is no operators around and the flexibility of payment in accordance with the volume of gasoline pumped out from dispenser. In addition, some modifications are also made toward the dispenser so that the dispenser is able to read the customer ID and communicate with the backend system of the mobile application. Implementation of this prototype is expected to improve service at SPBU by reducing queue time, improve company efficiency by reducing the number of operators in gas station. Furthermore, mobile applications can be utilized as communication channel with customers in order to improve customer engagement. In the long run, data obtained from recorded transactions can be used for various analyzes such as customer needs identification, loyalty program analysis, and provide additional services based on pattern captured from the data.